The Influence of Upstream and Downstream Supply Chain Management on the Indonesia Stock Exchange - Hamilah Hamilah (International Journal of Supply Chain Management, 2020)
Abstract— This study aims to analyze the effects of supply chain influence on initial Public Offering (IPO) and its implications on long term underperformance which is peroxided with the IHSG of IPO shares on the Indonesia stock exchange. IPO in this study is in 2016 with an analysis of 5 years period (2016-2020). The method used is the Purposive Sampling Method. Population implementation of the IPO in 2016 with a sample of 10 companies selected. Upstream and downstream supply chain phenomenon in this study made an IPO on the Indonesia stock exchange at 100% in the 2016 IPO. For the first analysis shows that the company age variable influences the SCM in the company that made an IPO in 2016 on the Indonesia stock exchange and simultaneously the age of the company, company size, capitalization, volatility, interest rate and rupiah exchange rate have a significant effect on SCM. For the second analysis, the variable long term underperformance in 2016 with a 5-year analysis (2016-2020) has a significant effect on the variable capitalization value, interest rate, and exchange rate of Rupiah. Simulate also include variable company age, company size, capitalization value, volatility, interest rate, dollar exchange rate and SCM stock price significantly influence. This study strengthens previous researchers that showed a high level of SCM, so supposedly the longer the company operates and improve the efficiency in long-term. Thus, firms’ managers could improve their performances by adopting plans and policies in the field of financial supply chain through the upstream, mid-stream and downstream in supply chains.